Evolving Food Choices Among the Urban Indian Middle-Class: A Qualitative Study - Kumar, Gargi S.; Kulkarni, Mrinmoyi; Rathi, Neha (Frontiers in Nutrition, 2022)
One of the leading risk factors for an escalating obesity burden in India is non-nutritious choices. Underpinned by the nutrition transition theory, this qualitative inquiry was designed to understand the urban middle-class Indian consumers’ views about processed foods and rapidly changing food choices. The study consisted of two phases, the first phase consisted of focus group discussions pertaining to the definition and conception of processed foods and the second phase consisted of interviews regarding the changing food environment. A convenience sample of Indian consumers aged 40–65 years were recruited from Mumbai and Kochi to participate in focus group discussions (FGD1 – nine participants and FGD2 – seven participants) and semi-structured face-to-face interviews (N = 22). Both discussions and interviews were audio-recorded and transcribed verbatim. Thematic analysis was used to analyze the transcribed data. Features of processed foods mentioned were chemical and physical processing, prolonged shelf life and poor nutritional quality. Factors influencing food choices and consumption of processed foods reported by participants could be categorized into changes in the socio-cultural environment and changes in the food environment. Changes in the socio-cultural environment included globalization and urbanization, long work days and sedentary living, rise in income levels and decrease in household cooking. Changes in the food environment included increased availability and accessibility of processed foods, replacement of traditional Indian diet with Western food, food as indicators of status, food advertisements and convenience. These results are consistent with nutrition transition theory and provide useful direction for public health policies aimed at promoting healthy diets.